First-line systemic therapy for metastatic castration-sensitive prostate cancer: An updated systematic review with novel findings. (January 2021) - Ferro, Matteo; Lucarelli, Giuseppe; Crocetto, Felice; Dolce, Pasquale; Verde, Antonio; La Civita, Evelina; Zappavigna, Silvia; de Cobelli, Ottavio; Di Lorenzo, Giuseppe; Facchini, Bianca Arianna; Scafuri, Luca; Onofrio, Livia; et al.
Graphical abstract: Abstract: Although both docetaxel and androgen-receptor-axis-targeted (ARAT) agents have yielded survival improvements in combination with androgen deprivation therapy (ADT) compared to ADT alone in metastatic castration-sensitive prostate cancer (mCSPC) patients, the optimal therapeutic choice remains to be established. We analyzed estimates of the hazard ratios for death (OS-HRs) in patients treated in the first-line setting enrolled in the GETUG-AFU15, CHAARTED, STAMPEDE, LATITUDE, ENZAMET, and TITAN trials. Overall, men with mCSPC receiving ADT with vs. without either an ARAT agent or docetaxel as first-line systemic therapy showed a pooled OS-HR of 0.69 (95 % CI: 0.61−0.78), with significant heterogeneity (p = 0.045, I 2 = 52.5 %). Network meta-analysis showed an OS-HR in patients receiving an ARAT agent vs. docetaxel of 0.78 (95 %CI: 0.67−0.91). In conclusion, the evidence analysed indicates that an ARAT agent may provide improved OS outcomes compared to docetaxel. Prospective randomized trials are warranted.